PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP AGRESIVITAS PAJAK (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2016) - Vinita Crysentia Narwadan (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine the effect of corporate characteristics on corporate tax aggressiveness. This research uses manufacturing companies food and beverage sub-sector listed on Indonesia Stock Exchange 2014-2016 as population. This study using purposive sampling technique, the selected data as sample is 36. Independent variables in this research consist of liquidity, leverage and capital intensity. The data were analyzed by using multiple regression and showed that leverage has a positive effect on tax aggressiveness. While for liquidity and capital intensity does not affect the level of tax aggressiveness. Keywords: liquidity, leverage, capital intensity, tax aggressiveness